Cuadrillas y montoneras en el conflicto campesinoindígena del altiplano jujeño (Argentina) en la década de 1870 - Fandos, Cecilia (Pontificia Universidad Católica del Perú, 2026)
This study examines the political participation of Puna populations through their role as soldiers in the National Guard during Argentina’s turbulent decade in the 1870s. It explores events and contexts linked to processes of state militarization, particularly the formation of armed squads and montoneras, as well as behaviors classified as seditious within the framework of the campesino–indigenous uprising for land. The research is grounded in the conceptual framework of «armed citizenship», revealing local forms of agency and negotiation, alongside an active engagement with state institutions.

En este estudio, analizamos la participación política de las poblaciones de la Puna de Jujuy mediante su rol como soldados de la Guardia Nacional durante la convulsionada década de 1870. Se examinan eventos y contextos asociados a los procesos de militarización estatal, especialmente vinculados a la conformación de cuadrillas y montoneras, así como a comportamientos calificados de sediciosos, en el marco del levantamiento campesino-indígena por la tierra. La investigación se inscribe en el marco conceptual de la «ciudadanía armada» y evidencia formas locales de agencia y negociación, así como una inserción activa en las instituciones estatales.
Cuadrillas and montoneras in the peasant-indigenous conflict of the Jujuy highlands (Argentina) in the 1870s
Keywords: 19th century; Citizens in arms; Politics; Indigenous territories; Siglo XIX; Ciudadanos en armas; Política; Territorios indígenas; https://purl.org/pe-repo/ocde/ford#6.01.01